Hubungan antara Pengetahuan, Sikap, dan Media Massa terhadap Perilaku Kesehatan Reproduksi pada Remaja Putri di SMA YPK Merauke - Karmiati Karmiati; Marni Br Karo; Titus Tambaip; Erni Agit Ekawati (JURNAL BIDANG ILMU KESEHATAN, 2023)
Teenagers are a group of people who are at risk of experiencing reproductive health problems. The aim of this research was to assess the relationship between knowledge, attitudes and mass media on reproductive health behavior at SMA YPK Merauke. This research uses an analytical observational research design with a cross sectional approach. With the total sampling technique, a sample of 80 respondents was obtained, the independent variables (knowledge, attitudes and mass media) and the dependent variable (reproductive health behavior) used a questionnaire. The Chi-Square statistical test was used to determine the relationship between variables. The results of the research show that there is a relationship between knowledge and reproductive health behavior (p value = 0.003), there is no relationship between attitudes and reproductive health behavior (p value = 0.964), and there is a relationship between media access and reproductive health behavior (p value = 0.006) . There is a need for health counseling and education for adolescents regarding reproductive health issues, and there is also a need for supervision and attention from parents and teachers.Keywords : knowledge, attitudes, mass media, reproductive health behavior